Ligand compatibility of salacinol-type α-glucosidase inhibitors toward the GH31 family. Issue 6 (15th January 2021) - Ishikawa, Fumihiro; Hirano, Aiko; Yoshimori, Yuuto; Nishida, Kana; Nakamura, Shinya; Takashima, Katsuki; Marumoto, Shinsuke; Ninomiya, Kiyofumi; Nakanishi, Isao; Xie, Weijia; Morikawa, Toshio; Muraoka, Osamu; et al.
Abstract : Salacinol-type α-glucosidase inhibitors are ligand-compatible with the GH 31 family. Salacinol and its 3′- O -benzylated analogs inhibit human lysosomal α-glucosidase at submicromolar levels. Abstract : We show that salacinol-type α-glucosidase inhibitors are ligand-compatible with the GH 31 family. Salacinol and its 3′- O -benzylated analogs inhibit human lysosomal α-glucosidase at submicromolar levels. Simple structure-activity relationship studies reveal that the salacinol side-chain stereochemistry significantly influences binding to GH31 α-glucosidases.